Global agricultural lands in the year 2015 - Z. Mehrabi; Z. Mehrabi; Z. Mehrabi; K. Tong; K. Tong; J. Fortin; J. Fortin; J. Fortin; R. Stanimirova; M. Friedl; N. Ramankutty; N. Ramankutty (Earth System Science Data)
While there are many global geospatial datasets representing the extent of agriculture, they predominantly represent croplands. Only a couple of global data products represent the full global agricultural footprint, including both cropland and pastures. Our own research team's most recent complete publicly available agricultural land cover dataset, including both croplands, and pastures, represents circa 2000. These data, distributed on a graticule of 5 arcmin (∼ 10 km2 at the Equator), have been integrated into a considerable number and diversity of research studies, modelling, data science, and media applications. Further, users of these data have been interested in them for studying a variety of issues such as land use, food security, climate change, and biodiversity loss. Here we present an updated dataset on the global distribution of agricultural lands (cropland and pasture) circa 2015 (15 years on since the initial study). Past studies that have constructed such datasets have been one-off exercises that have been infrequently repeated due to the amount of effort required. Therefore, in this work, we developed a transparent and reproducible approach to update our data product while also enabling easier reproduction of future datasets. We distribute our 2015 product at the same resolution and formats as the prior product, and accompany it with a full set of replicable code and data for reconstruction. In this article we explain how the data was constructed, with links to the permanent DOIs where the data can be readily downloaded by the user community (Mehrabi et al., 2024; https://doi.org/10.5281/zenodo.11540553).